Modelling Chemical Composition / Temperature Effects on Glass-Reinforced Laterite Bricks via D-Optimal Design - Saliou, Njuhou; Kaze, Cyriaque Rodrigue; Richard, Mache Jacques; Ramadan, Njindam Oumarou; Cengiz, Özgur; Dayirou, Njoya (Engineering Science & Technology, 2025)
The effect of SiO2, Fe2O3, (CaO + Na2O), and firing temperature on the characteristics of lateritic clay bricks produced using lateritic clay and recycled waste glass powder was investigated. The mixture was prepared and subjected to firing at 750 and 1,000 °C. The by-products were characterized by their linear shrinkage, flexural strength, porosity, and mineralogy. The flexural strength equation demonstrates a synergistic beneficial interaction between SiO2 and (CaO + Na2O), which increased the flexural strength, and an antagonistic interaction between Fe2O3, (CaO + Na2O), and temperature from 750 to 1,000 °C, which decreased flexural strength by the formation of sillimanite Al2O3. In addition, the diffusion process of iron due to temperature led to the substitution of alumina in sillimanite to form (Al,Fe)2SiO5 and decreased the flexural strength. The linear shrinkage equation demonstrates a synergistic interaction between Fe2O3 and temperature, which increased the linear shrinkage. The X-Ray Diffraction (XRD) patterns indicated the presence of hematite, quartz, cristobalite, and sillimanite as the main crystalline phases. The optimal mixture, which meets the desired requirements (porosity ≤ 20%, flexural strength ≥ 4 MPa, and linear shrinkage ≤ 2%), is chemically composed of 34% SiO2, 37% Fe2O3, 14.5% Al2O3, 3% (CaO + Na2O), and 10.5% loss on ignition. The corresponding formulation in terms of raw materials is 78% lateritic clay and 22% glass powder, sintered at 888 °C.